ANALISA KINERJA MONITORING SUHU DAN KELEMBAPAN TANAH BERBASIS IOT PADA ALAT PENYIRAMAN OTOMATIS TANAMAN CABAI DI DALAM GREEN HOUSE - Faisal Adi Putra Tomyka Ode; Eka Purwa Laksana; Nifty Fath; Suwasti Broto; Indra Riyanto (MAESTRO, 2023)
Chili plants really need to be considered both in terms of planting or watering, but they really need a place that has good soil levels and an ambient temperature that is not too hot or cold. If these plants can be watered automatically, it is likely that the quality of the plants will be good and will get good results. This study aims to design an automatic watering device that will be monitored remotely so that soil moisture is maintained. Where this final project has designed an automatic watering device and keeps the temperature inside the Green House automatically based on IoT and a monitoring system based on several prototypes controlled by Arduino mega2560 and NodeMCU ESP8266 as a data sending tool and connecting to Thinger.io which functions to display data, the pump will active to water the plants when the sensor value reading is above or more than 70% and the pump will stop when the sensor reading value is below or more than 50%, then the fan will turn on when the temperature value inside the green house is more than 28 degrees Celsius and the fan will turn off when the temperature value inside the green house is less than 28 degrees Celsius. The Soil Mousture sensor functions as a reader of the humidity value in chili plants and the DHT11 sensor as a reader of the temperature value in the Green House. Based on the TIPHON standard, QoS testing of monitoring system communications is included in the good category, for throughput testing the index value is 4, packet loss index value is 4, delay index value is 1, and jitter index value is 1.